Dual‐Scale Integration Design of Sn–ZnO Catalyst toward Efficient and Stable CO2 Electroreduction (Adv. Mater. 38/2022). Issue 38 (23rd September 2022) - Ren, Bohua; Zhang, Zhen; Wen, Guobin; Zhang, Xiaowen; Xu, Mi; Weng, Yueying; Nie, Yihang; Dou, Haozhen; Jiang, Yi; Deng, Ya‐Ping; Sun, Guiru; Luo, Dan; et al.
Abstract : CO2 Electroreduction It remains challenging to increase the energy efficiency while maintaining long durability of catalysts for CO2 electroreduction to CO. In article number 2204637, Xin Wang, Ming Feng, Aiping Yu, Zhongwei Chen, and co‐workers demonstrate a dual‐scale delicate design of a non‐noble Sn–ZnO active interface inserted into nanopores of high‐surface‐area carbon nanospheres, through d‐bandwidth tuning and nanoconfinement tailoring to develop efficient and stable CO2 electroreduction.